Giving space to the subject's potential present: Zemelman's contributions to Sociology of Education - Acuña, Felipe; Corbalán, Francisca (British journal of sociology of education, 2023)
The subfield of Sociology of Education (SOE) concerned with the growth of neoliberalism through critically analysing its policies, discourses, and processes of subjectivation has made a significant contribution to education in the last 40 years. Whilst this scholarship has generated new knowledge about what happens to people, contexts and educational systems when they are regulated by neoliberal logics, it has also subsumed the sociological imagination under what this episteme considers valuable. The paper aims to challenge this excessive focus on the neoliberal episteme by broadening our research scope to recover the subjects' magmatic expression in SOE research. To do this, we introduce Hugo Zemelman's notion of subject to examine how SOE can overcome this neoliberal closure. The paper discusses three epistemic movements: focusing on the subject, researching the undetermined possibilities of the present in a given order, and, paying attention to the evocative and symbolic aspects of thinking and language.